2002
DOI: 10.1093/aje/155.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Medication Use and Risks of Gastroschisis and Small Intestinal Atresia

Abstract: Gastroschisis and small intestinal atresia (SIA) are birth defects that are thought to arise from vascular disruption of fetal mesenteric vessels. Previous studies of gastroschisis have suggested that risk is increased for maternal use of vasoactive over-the-counter medications, including specific analgesics and decongestants. This retrospective study evaluated the relation between maternal use of cough/cold/analgesic medications and risks of gastroschisis and SIA. From 1995 to 1999, the mothers of 206 gastros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
153
9
13

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(181 citation statements)
references
References 10 publications
6
153
9
13
Order By: Relevance
“…Still, this finding was unexpected, considering the relatively young pregnant population in AO compared to in Norway. Misclassifications of gastroschisis as omphalocele in AO could be an explanation for the ratio difference (7,8). Since our study only included cases registered as isolated, under-diagnosing of anomalies cooccurring with omphalocele, such as heart defects (4), could also be an explanation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, this finding was unexpected, considering the relatively young pregnant population in AO compared to in Norway. Misclassifications of gastroschisis as omphalocele in AO could be an explanation for the ratio difference (7,8). Since our study only included cases registered as isolated, under-diagnosing of anomalies cooccurring with omphalocele, such as heart defects (4), could also be an explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was a strength of our study that information about induced and spontaneous abortions from as early as weeks' gestation was available. Reported studies concerning severe birth defects in relation to maternal age usually did not include spontaneous abortuses with less than 0 or 4 weeks' gestation (5,9,0,7,8); they only included medically induced abortuses (0), or abortuses were not included at all (8). Earlier studies of these defects in Norway did not include medical abortions and spontaneous abortuses with -6 weeks' gestation (9,7,).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] Additional risk may occur when combinations of these medications are used. 14 Torfs et al 15 demonstrated that teenage diets, with lower intake of a-carotene, total glutathione, and high levels of nitrosamines, were associated with increased risk of gastroschisis.…”
Section: Rising Birth Prevalence Of Gastroschisismentioning
confidence: 99%
“…Young maternal age is the most consistently reported risk factor (Baerg et al, 2003;Feldkamp et al, 2007;Hougland et al, 2005;Saada et al, 2005). Other maternal factors that have been suspected to increase gastroschisis risk include maternal smoking, maternal use of vasoactive substances, low socioeconomic status, low pregnancy body mass index, and Hispanic ethnicity (Haddow et al, 1993;Torfs et al, 1994;Lam et al, 1999;Werler et al, 2002;Salihu et al, 2003;Saada et al, 2005;Canfield et al, 2006;Feldkamp et al, 2007;Stothard et al, 2009). More recently, maternal birthplace (nativity) has been reported to affect the risk of congenital malformations, including gastroschisis; foreign-born women have a lower risk of delivering an infant with gastroschisis than U.S.-born women (Zhu et al, 2006;Vu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%